Coir pith compost is a suitable substrate for mass multiplication of true cinnamon (Cinnamomum verum J. Presl.) - Waman, Ajit Arun; Bohra, Pooja; Karthika Devi, R.; Isac, Sheena (Journal of Plantation Crops, 2025)
True cinnamon has been valued for multifaceted applications in pharma, aroma and food industries. Use of seedling progenies for establishment of commercial plantations result in production of non-uniform quality raw material. Hence, adoption of improved varieties and vegetative propagation is desirable. Further, to multiply superior germplasm in crop improvement programmes, vegetative propagation is the norm. However, being a difficult-to-root species, use of air layering is a viable option. The present study aimed at understanding the effect of substrates (coir pith compost and soil: farmyard manure) on air layering in four improved varieties of true cinnamon. Coir pith compost was reported to support better root induction (%), root growth, and post-separation establishment; with genotype-dependent variations. Highly significant interaction effects between genotypes and substrates were evident. Additionally, the study was extended to know the suitability of coir pith compost for 23 accessions of cinnamon, which revealed that the responding layers (with rooting/ callusing) ranged between 50 and 100%. A total of 78.3% accessions showed minimum of 70% responding layers thereby proving the practical utility of the method in field collection work. Hence, coir pith compost could be recommended for large-scale air layering of improved varieties of true cinnamon apart from multiplication of superior germplasm.